THE VALUES OF MORAL EDUCATION IN THE NOVEL BUNDA CINTA STORY 2 KODI BY ASMA NADIA - Marianti; Kaspullah; Suriadi (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
The focus of this research is what values of moral education are contained in the novel Bunda Kisah Cinta 2 Kodi by Asma Nadia and how is the relevance of moral education in the novel Bunda Kisah Cinta 2 Kodi by Asma Nadia in madrasah/elementary schools. The aim of this research is to describe and analyze the values of moral education in the novel Cinta 2 Kodi by Asma Nadia. To describe the relevance of moral education in the novel "Bunda Kisah Cinta 2 Kodi" by Asma Nadia in madrasah/elementary schools. This research uses a qualitative approach and library research type of research (Library Study Research). Data collection techniques use documentation techniques. The data analysis technique used is content analysis. The research results show that; (1) The values of moral education contained in the novel "Bunda Kisah Cinta 2 Kodi" by Asma Nadia are sincerity, piety, gratitude, honest repentance, hard work, responsibility and love; (2) The relevance of moral education in the novel "Bunda Kisah Cinta 2 Kodi" by Asma Nadia in madrasah/elementary schools. Learning Aqidah Morals, especially at the basic level, is one of the keys to the process of forming the Islamic personality and morals of the next generation, which is in accordance with Islamic teachings because it is at the basic level that Islamic values are first taught.